Formas de enfrentamento à criminalidade organizada - Costa, Rodrigo de Campos (2011)
The purpose of this paper is to analyse Criminal Law in relation to the fight against organized crime. The evolution of Criminal Law was outlined, starting with the main penal schools and also with the dogmatic lines of thought, from Causalism to Functionalism. Considering the legal interest as Criminal Law's main objective, parameters based on constitutional values were established for its definition. The analysis of the legal interest was double folded, having been classified as being of both individual and universal nature, thus enabling the defence of the constitutionality of crimes of abstract danger. The warrants of criminalization, whose fundamentals oblige the infra-constitutional legislator to protect the legal interest elected by the Constitution, were object of analysis. As for organized crime, its evolution as a social and legal phenomenon was analysed, focusing on the history of Brazilian legislation, from the Imperial Penal Code to today's Law 9.034/95. The analysis of the concept of organized crime was based on the concept taken from the Palermo Convention, more open and permissive, so as not to restrict legislation on the account of the effects of the advance of globalization. Thus, in order to establish the concept of organized crime, its characteristics were identified insisting on the need for legal definition. The investigation tools of the Law 9.034/95 were also analysed, following legitimizing arguments. Lastly, the Enemy's Criminal Law and the Right to Safety were analysed as ways to interpret and provide justification for legislations both from penal as well as processual order in the fight against organized crime. From the research done, we conclude for the interpretation of the Right to Safety as a fundamental right, in its objective acception, based on imperatives of tutelage. The collision between constitutional principles must be solved through the application of the principle of proportionality